The Concept of Data Model Pattern Based on Fully Communication Oriented Information Modeling (FCO-IM) - Fazat Nur Azizah; Benhard Sitohang; Guido P. Bakema; Oerip S. Santoso (LPPM ITB, 2010)
Just as in many areas of software engineering, patterns have been used in data modeling to create high quality data models. We provide a concept of data model pattern based on Fully Communication Oriented Information Modeling (FCO-IM), a fact oriented data modeling method. A data model pattern is defined as the relation between context, problem, an d solution. This definition is adopted from the concept of pattern by Christopher Alexander. We define the concept of Information Grammar for Pattern (IG P) in the solution part of a pattern, which works as a template to create a data model. The IG P also shows how a pattern can relate to other patterns. The data model pattern concept is then used to describe 15 data model patterns, organized into 4 categories. A case study on geographical location is provided to show the use of the concept in a real case.